Performance of Self-Compacting Concrete (SCC) Mixes with Different Brands of Superplasticizers - Asep Hilmansyah (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2025)
Self-Compacting Concrete (SCC), classified as High-Performance Concrete (HPC), is a type of cement-based concrete characterized by its high flowability, ability to compact without vibration, and resistance to segregation. These properties make SCC ideal for structures with dense reinforcement or complex cross-sections. The use of a Superplasticizer admixture is essential in producing SCC with the required performance. This study aimed to analyze the influence of three Superplasticizer brands—NAPTHA 600D, NORMET TanCem 60RP, and CONSOL P200-R 1S—on the characteristics and performance of SCC. The experimental work was conducted at the Laboratory of Geotechnics, Tunnels, and Structures (BGTS) of the Road and Bridge Engineering Implementation Unit. Three dosage variations (0.5%, 0.7%, and 1.0%) were tested to evaluate homogeneity, slump flow, and compressive strength. The slump flow was controlled according to the Bina Marga General Specifications 2018 Revision 2 (550–850 mm), and the compressive strength was targeted at 33 MPa at 7 days. The results showed that all Superplasticizers produced different flowability and strength characteristics. At 1.0% dosage, each brand achieved the required slump flow and compressive strength, with minor variations in homogeneity and bleeding behavior.